2021
DOI: 10.1186/s12985-021-01487-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile during occult hepatitis B virus infection in chronic hepatitis C patients

Abstract: Background The hepatitis B virus (HBV) is one of the leading causes of acute, chronic and occult hepatitis (OBI) representing a serious public health threat. Cytokines are known to be important chemical mediators that regulate the differentiation, proliferation and function of immune cells. Accumulating evidence indicate that the inadequate immune responses are responsible for HBV persistency. The aim of this study were to investigate the cytokines IFN-γ, TNF-α, IL-2, IL-4, IL-6, IL-10 and IL-1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 76 publications
2
14
0
1
Order By: Relevance
“…These findings were consistent with the existing literature; e.g., in their research, Ribeiro C.R.A. et al (2021) found high serum levels of IL-10, IL-4, IL-2 and TNF-α in HCV patients compared with controls [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings were consistent with the existing literature; e.g., in their research, Ribeiro C.R.A. et al (2021) found high serum levels of IL-10, IL-4, IL-2 and TNF-α in HCV patients compared with controls [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…The individuals diagnosed with HCV are highly prone to tooth decay as well as periodontal diseases, which can affect their dietary intake, leading to a poor quality of life [ 6 , 9 , 10 , 11 , 12 ]. A meta-analysis [ 13 ] revealed increased gingival bleeding among patients with HCV compared to a non-HCV group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, the chronic inactive HBV infection was not associated with increased IFN-γ and IFN-λ. 23,24 However, our study significantly correlated high levels of IFN-γ and granzyme B with increased viral load. Granzyme B is one of the NK cell weapons, which can mediate liver cell damage and increase HBV load.…”
Section: Discussionmentioning
confidence: 50%
“…Increased apoptosis may thus play a role in the occurrence of OBI[ 39 , 61 , 62 ]. A more recent study found that in patients with OBI and chronic HCV infections compared with monoinfected (HCV) patients and healthy donors, the levels of TNF-α, IL-10, IL-6, IL-4, and IL-2 were increased[ 63 ]. Vitamin D3 and vitamin D receptor (VDR) regulate several cytokines and are important determinants of anti-HBV response.…”
Section: Mechanisms That Lead To Obimentioning
confidence: 99%